Fecundity and gonado somatic index of Gangetic mud eel, Monopterus cuchia (Hamilton, 1822) - Chakraborty, Binay K; Azad, SA; Barman, B; Faruque, AMO (Bangladesh Journal of Zoology, 2015)
The gonado-somatic index (GSI) and fecundity of Gangetic mud eels Monopterus cuchia (Hamilton, 1822) were investigated during January to December, 2010 at Sherpur, Bangladesh. Highest GSI value was found in the month of June and the values began to fall gradually from July to December in both sexes. The fecundity ranged from 458.0±31.22 to 1116.0±11.31 in 62 samples having a total length of 54.25±1.71 to 66.05±0.71 cm, body weight from 256.33±45.14 to 492.50±2.50 g and gonad weight from 21.32±4.48 to 55.90±0.98 g. The relationships between body length and fecundity was found to be polynomial of second order of body weight and was expressed as: Y=0.2683 X2- 1.9383 X+370.72. The regression equation established for fecundity on total body weight was Y=454.37 X-692.8. The regression equation established for fecundity on total gonad weight was Y=19.602 X-27.546. The above equation showed that the relationships between fecundity and total weight was curvilinear. A highly significant (P<0.01) linear relationship was found to exist between fecundity and gonadal weight. Bangladesh J. Zool. 41(2): 165-172, 2013